Oxytocin and Epstein‐Barr virus: Stress biomarkers in the postpartum period among first‐time mothers from São Paulo, Brazil. Issue 1 (22nd November 2013) - Rudzik, Alanna E.F.; Breakey, Alicia; Bribiescas, Richard G.
ABSTRACT: Objectives: The purpose of the study was to examine the relationship between self‐reported stress levels among new mothers in São Paulo, Brazil and two biomarkers of stressful experience, oxytocin (OT) and Epstein‐Barr Virus antibody level (EBV‐ab), with planned pregnancy hypothesized as a moderator of biological response to stressful conditions. Methods: Sixty‐three first‐time mothers between the ages of 15 and 45 were recruited from neighborhoods in São Paulo, Brazil. Quantitative and qualitative data were collected longitudinally, bi‐weekly between two and 12 weeks postpartum. OT level was assessed from breast milk samples and EBV‐ab from blood spot samples. An Interpersonal Satisfaction scale was developed, validated, and administered, along with the Cohen perceived stress scale (PSS). Results: In‐depth interview data revealed unplanned pregnancy to be a significant stressor in the lives of first‐time mothers. In linear regression, OT level was negatively associated with interpersonal satisfaction score ( P  = 0.022) and positively associated with PSS score ( P  = 0.007). When splitting the sample by planned status of the pregnancy, women with an unplanned pregnancy showed a strengthened positive association between OT level and PSS ( P  = 0.001; Adj R 2  = 0.44) and negative association with interpersonal satisfaction ( P  = 0.017; Adj R 2  = 0.15), while no associations existed for women with a planned pregnancy. EBV‐ab level was not correlated or associated with stress/satisfaction measures. Conclusion: OT is an effective biomarker in the measurement of stress in the body, and additionally reflects differential experiences with difficult interpersonal circumstances, such as unplanned pregnancy. By contrast, EBV‐ab failed to reflect differences in self‐reported stress levels between mothers. Am. J. Hum. Biol. 26:43–50, 2014. © 2013 Wiley Periodicals, Inc.